Enhance Data Integrity For Data Storage In Cloud Computing - Shiva Krishna, Maddhukuri.; D, Sravani; Triveda.B, Anjana (International Journal of Engineering and Technology, 2018)
In this paper, a well secured and effective AES based framework is proposed for proposed for evaluating individual records put away at the untrusted server. The gadget guarantees the of certainties respectability and accessibility. The gadget bolsters open reviewing with the guide of using TPA and privateness holding by a method for not releasing the data to TPA amid trustworthiness check system. Through regular respectability checking, the machine guarantees records ownership at a remote server.Â Â